Foreign aid allocation, governance, and economic growth - Akramov, Kamil (EBL-Schweitzer, 2012)
Kamiljon T. Akramov investigates the effectiveness of foreign aid to developing countries by comparing the results of aid allocated to a recipient's production sectors, economic infrastructure, or social sectors.